The Effectiveness of Google Sites-Based Teaching Modules in Learning the State of Matter and Its Changes in Elementary Schools - Heni Septiani; Mislan Mislan; Jetra Viktoria (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aimed to examine the effectiveness of a Google Sites–based teaching module in delivering the topic of states of matter and their changes to fourth-grade students at SDN 72/IX Pematang Jering. The research applied the Research and Development (RnD) method using the ADDIE development model, which includes analysis, design, development, implementation, and evaluation stages. The participants consisted of 17 students, with 6 students involved in the small-group trial and all students participating in the field trial. Data were collected through product trials, student response questionnaires, and classroom observations during the learning process. The evaluation focused on the module’s attractiveness, ease of use, and clarity of the material presented. The findings revealed that the Google Sites–based module achieved a validity score of 96.6%, categorized as highly valid. In addition, the module increased students’ motivation, participation, and understanding of the concepts. Therefore, the module is considered suitable as an innovative and interactive learning medium for elementary school students.